Efektivitas Citicoline sebagai Terapi Gangguan Kognitif pada Stroke Iskemik Akut - Lothar Matheus Manson Vanende Silalahi; Pradita Sri Mitasari (PT Kalbe Farma Tbk., 2024)
Background: Cognitive impairment in acute ischemic stroke is associated with disability, poor functional outcome, and mortality, hence requires effective management. Citicoline is one of pharmacotherapy for central nervous system disorders. This study aims to evaluate current evidence of the effectiveness of citicoline for cognitive impairment in acute ischemic stroke. Methods: Systematic review and meta-analysis on randomized controlled trials searched in PubMed, Cochrane, and Google Scholar databases. Screening was done on 518 articles according to inclusion and exclusion criteria, 3 articles were qualified for review. Results: Cano-Cuenca, et al, (2015) found that citicoline was associated with a mini-mental state examination (MMSE) score of >25 at 12 weeks. Pinzon & Asanyi (2018) found that the use of citicoline can prevent cognitive impairment at 6 and 12 months, especially in attention and temporal orientation. Bonvicini, et al, (2022) found that citicoline is associated with good cognitive outcomes as measured with global cognitive impairment. Conclusion: Citicoline is effective as a therapy for cognitive impairment in acute ischemic stroke.